2021
DOI: 10.3389/fmicb.2021.641317
|View full text |Cite
|
Sign up to set email alerts
|

The Phage Nucleus and PhuZ Spindle: Defining Features of the Subcellular Organization and Speciation of Nucleus-Forming Jumbo Phages

Abstract: Bacteriophages and their bacterial hosts are ancient organisms that have been co-evolving for billions of years. Some jumbo phages, those with a genome size larger than 200 kilobases, have recently been discovered to establish complex subcellular organization during replication. Here, we review our current understanding of jumbo phages that form a nucleus-like structure, or “Phage Nucleus,” during replication. The phage nucleus is made of a proteinaceous shell that surrounds replicating phage DNA and imparts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Our updated model for jumbo phage replication, shown in Fig. 6 together with our proposed model ( 40 ), begins with the attachment of phage to the host cell and injection of viral DNA. The expression of the nuclear shell protein occurs immediately after injection to form an enclosure around phage DNA that provides a safe compartment for DNA replication to occur.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our updated model for jumbo phage replication, shown in Fig. 6 together with our proposed model ( 40 ), begins with the attachment of phage to the host cell and injection of viral DNA. The expression of the nuclear shell protein occurs immediately after injection to form an enclosure around phage DNA that provides a safe compartment for DNA replication to occur.…”
Section: Resultsmentioning
confidence: 99%
“…Viral capsid proteins assemble on the membrane midway through the infection cycle and are transported by treadmilling PhuZ filaments to the phage nucleus, where they dock to initiate DNA packaging. Treadmilling filaments rotate the phage nucleus to allow capsids to be evenly distributed on its surface ( 40 ). Once capsids are full of viral DNA, they coassemble with tails and form bouquets containing what appear to be mature particles.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that different Pseudomonas phages isolated at different periods and from distant geographical areas contain high genome sequence similarities. For example, distinct giant phages that were classified in different families (siphophage SD1-M and nucleus-forming myophage phiKZ) shared a very high genome identity up to 99% with only two DNA segments different between their genomes ( Kwan et al, 2006 ; Krylov et al, 2007 ; Chaikeeratisak et al, 2021 ). Specifically, in the Pbunavirus genus, PB1-like phages, which are the very common virulent P. aeruginosa phages, shared a remarkable genome similarity to one another (over 95%).…”
Section: Discussionmentioning
confidence: 99%
“…Subcellular organization is essential for all domains of life, including viruses ( Chaikeeratisak et al, 2021a ; Charman and Weitzman, 2020 ). We recently identified a nucleus-like structure ( Chaikeeratisak et al, 2017b ) formed by Pseudomonas chlororaphis jumbo phage 201φ2–1 ( Thomas et al, 2008 , 2010 , 2012 ), which was subsequently shown to be conserved ( Chaikeeratisak et al, 2017a ; Danilova et al, 2020 ) in related phages ΦKZ ( Krylov et al, 2021 ; Lecoutere et al, 2009 ; Mesyanzhinov et al, 2002 ; Weintraub et al, 2019 ), and ΦPA3 ( Monson et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%